Publication strategies for monographs in HSS: 4eu+ - Nissen, Martin; Pauplin, Pascale (Zenodo, 2022)
Through this online course, you will learn about the publishing process for academic books in Humanities and Social Sciences, from the planning of your publication strategy to the choice of publisher, the selection of the license, and peer-review. What should you expect? How does open access publication work?
Gesehen am 09.02.2022